Spiritual Care of Inpatients Focusing on Outcomes and the Role of Chaplaincy Services: A Systematic Review - Kirchoff, Robert W. (Journal of religion and health, 2021)
To identify demographic trends associated with patient utilization and healthcare provider request for spiritual care services and to describe the impact of spiritual care on the quality of life (QoL), spiritual well-being (SWB) and level of satisfaction (SAT) of hospitalized patients., A systematic search of Ovid MEDLINE, Embase, PsycINFO, Cochrane Central Register of Controlled Trials, Cochrane Database of Systematic Reviews, Scopus, was combined with review of relevant bibliographies. A total of 464 titles and abstracts were reviewed. Data were independently extracted by reviewers according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Data on the effects of spiritual interventions on QoL, SWB and SAT were extracted, along with demographic data reflecting chaplain services. The results of the studies are presented narratively and in a qualitative manner., Observational or experimental studies investigating chaplain utilization demographics (n = 12), patient satisfaction (n = 9) and QoL/SWB (n = 3) were included. Perceived severity of illness, average length of stay and older age were consistently found to be predictors of higher need for spiritual care. Receipt of spiritual care was correlated with increased patient and family satisfaction, independent of clinical outcome. Chaplain interventions were associated with improvement in perceived QoL and SWB. In spite of this, healthcare workers rarely attempt to explore the patient’s or family’s need for spiritual care, with the majority of chaplaincy consults occurring in the final day of the patient’s life, potentially leading to a failure to meet the spiritual needs of non-terminal patients who have spiritual trauma related to their resolving illnesses., Attention to the spiritual needs of hospitalized patients is an essential yet often overlooked aspect of patient care. Chaplains serve as spiritual care specialists whose services can enhance the hospital experience, improve patient satisfaction and help to bridge potential gaps between the patient and medical providers.